Effect of internal curing by super-absorbent polymer on hydration of hydrophobic cement-based material - Yunfeng Li; Qing Wang; Xu Zheng; Rui Zhang; Ning Wang (Scientific Reports)
Abstract Hydrophobic cement-based materials are a primary focus in current research due to their potential applications. Nevertheless, the presence of a hydrophobic layer often impedes the hydration process, resulting in reduced concrete strength. In this study, the use of super-absorbent polymer (SAP) to enhance the hydration degree of cement, thereby improving the mechanical properties of hydrophobic cement-based materials, was explored. SAP maintains the intrinsic hydrophobic characteristics of these materials while promoting cement hydration. The hydration degree was assessed using a combined approach of qualitative and quantitative analyses. The underlying mechanisms contributing to the enhanced material strength were elucidated through the calculation and analysis of the cement-air ratio. Additionally, the hydration heat release process was investigated through finite element simulation. The integration of SAP not only strengthens the material but also enhances its crack resistance, significantly broadening the potential applications of hydrophobic cement-based materials.